The competitive dynamics of strategic risk‐taking, unethical behavior, and entry - Ostler, James (Strategic Management Journal, 2025)
Abstract Research Summary This article argues that strategic risk‐taking in the form of unethical behavior can lead to successful entry and that this entry can drive incumbents to either adopt similar behavior or potentially be forced out of the market. Thus, entrepreneurs can introduce innovative, but socially destructive, behavior to a market and motivate its adoption by incumbents. Empirical support is found using a policy change in the liver transplant market to identify the use and adoption of unethical misrepresentation of patient health status. This article contributes to our understanding of entrepreneurial strategy as well as the competitive dynamics between entrants and incumbents in adopting new risky innovations and, in particular, unethical behaviors. Managerial Summary This article highlights the impact of strategic risk‐taking through unethical practices, showing how they can sometimes lead to a successful market entry. Successful entry can force existing market players to either follow suit or risk being forced out of the market. This study looks at the liver transplant market, where transplant centers took advantage of a previous policy by misrepresenting patient health status to move their patients to the top of the transplant list. The findings underscore the importance of understanding the competitive dynamics of adopting innovative yet ethically questionable strategies by both new entrants and established companies, offering valuable insights into how businesses navigate competitive pressures and ethical boundaries. It also highlights the importance of policymakers considering these competitive dynamics when setting policy.